Karakteristik Sosial Ekonomi Penghuni (Penyewa) dalam Perumahan Bersubsidi di Kecamatan Ungaran Timur - Diavinci Tri Surya; Asnawi Manaf (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Subsidized housing is expected to resolve residential backlog problems but in the provision of housing emerging new problems, it’s called the backlog of ownership. The purpose of this research is to know the preferences of residents (tenants) based on the physical occupancy and the level of interest in owning a subsidized housing by reviewing socio-economic characteristics such as education level, age, number of family members, population status, type of work, income level and total expenditure in subsidized housing. The study area chosen is in the District of East Ungaran by taking four subsidized housing namely Puri Delta 5, Panorama Asri, Villa Delia and Griya Bukit Jati Sari. The method used to determine the Socio-Economic Characteristics and Preferences in Owning Subsidized Housing is a quantitative method with data collection techniques using questionnaires and observations. The number of respondents spread over 4 housing is 41 respondents. The analysis technique used in this study is descriptive statistics using crosstab analysis. Based on the results of crosstab socioeconomic characteristics that have a relationship or a relationship with the reason for residents to rent is related to economic characteristics such as the type of work, the amount of income and monthly expenditure of tenants.